2011
DOI: 10.5586/asbp.2004.045
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of seedling recruitment in experimental gaps on mosaic vegetation of abandoned meadows

Abstract: The paper presents results of a study on the response of species growing in experimental gaps in the patches dominated by Carex acutiformis, C. cespitosa and Salix cinerea. The study was performed in a meadow area subjected to the process of succession in the Reski Range in the Bia³owieski National Park. Four patterns of seedlings recruitment in the experimental gaps were distinguished: pattern I great number of seedlings with high richness of species, pattern II great number of seedlings with low richness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…However, in the case of species with spongy, brittle rhizomes, like in the studied C. rivulare, large patches disintegrate. This enables the ger- mination of seeds and the development of seedlings in the newly created gaps (Borkowska, 2004). Despite a high density of ramets and their close proximity in a patch, we found that they had a high level of genetic differentiation, which resulted in high values of heterozygosity and the polymorphism information content (PIC) index.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in the case of species with spongy, brittle rhizomes, like in the studied C. rivulare, large patches disintegrate. This enables the ger- mination of seeds and the development of seedlings in the newly created gaps (Borkowska, 2004). Despite a high density of ramets and their close proximity in a patch, we found that they had a high level of genetic differentiation, which resulted in high values of heterozygosity and the polymorphism information content (PIC) index.…”
Section: Discussionmentioning
confidence: 97%
“…At present, C. rivulare is most abundantly represented in macroforbs in the initial stage of succession. The population is characterised by a repeated seedling recruitment pattern (Eriksson, 1989;Borkowska, 2004).…”
Section: Samplingmentioning
confidence: 99%
“…Accumulating necromass (produced by mortifying ramets) might also have limited seed germination on tussock cores. It has been repeatedly found that disruption of the vegetation cover and changes in microhabitat conditions relocate seeds to the soil surface and allow their germination (Thompson and Grime 1979;Thompson 1992;Łaska 2001;Borkowska 2004). Field observations (unpublished data) and the results of this study show that tussocks rarely contain other (growing) species.…”
Section: Discussionmentioning
confidence: 49%
“…The abundant colonisation of openings in swards by seedlings of T. europaeus was observed previously by several authors (Hitchmough 2003;Vandvik 2004;Kochanowska & Gamrat 2007;KostrakiewiczGierałt 2012). At the same time, it should be pointed out that the role of disturbances as safe sites for the recruitment of clonal plant seedlings in meadows was demonstrated repeatedly (Eriksson 1997;Borkowska 2004;Kostrakiewicz-Gierałt 2014a). On the other hand, animal activities such as wallowing, trampling and browsing may lead to uprooting genets of T. europaeus or damage to their above-ground parts.…”
Section: Abundance and Developmental Structure Of Subpopulationsmentioning
confidence: 99%